Peningkatan Kompetensi Siswa SMK Melalui Pelatihan Junior Web Developer Dalam Pengembangan Website - Ade Irma Purnamasari; Yudhistira Arie Wijaya; Aditiya Arif Firmansyah; Intan Wangi Nur Qibti (CV. Multi Kreasi Media, 2024)
This community service program aims to enhance the competencies of vocational high school (SMK) students in web development through a Junior Web Developer training program. The activities were carried out at several SMKs in Cirebon Regency and Cirebon City as an effort to bridge the gap between school curricula and industry needs. The implementation methods included preparation and planning, training execution, monitoring and evaluation, as well as dissemination of results. The outcomes of this program showed a significant improvement in students' understanding and skills in web development technologies, particularly in the use of HTML, CSS, JavaScript, and modern frameworks. In addition, participating teachers also benefited from workshops designed to enhance their ability to teach industry-based materials. This program successfully produced several outputs such as learning modules, student web projects, and collaborations with industry partners to open up job opportunities for graduates. With this program, it is expected that vocational students will have better competencies to face the workforce and the digital industry. The sustainability of this program can be expanded by increasing industrial partnerships and broadening the scope of training participants.